Before the Gregorian Reform : The Latin Church at the Turn of the First Millennium - Howe, John, 1947 March 13- (Book collections on Project MUSE., 2016)
Historians typically single out the hundred-year period from about 1050 to 1150 as the pivotal moment in the history of the Latin Church, for it was then that the Gregorian Reform movement established the ecclesiastical structure that would ensure Rome's dominance throughout the Middle Ages and beyond. This book challenges this familiar narrative by examining earlier, "pre-Gregorian" reform efforts within the Church.